AACSB-Accreditation benefits as predictor of faculty attitude toward the accreditation process: an exploratory study - Tawfik Mady, M.; Al-Hussainan, Adel; Tawfik Mady, Tarek (Journal of Management and Business Education, 2023)
The purpose of the study is to investigate the attitude of faculty members of the College of Business Administration at Kuwait University (CBA-KU) toward the AACSB accreditation system and the way they perceive the benefits of accreditation. The level of association and the causal effect of perceived benefits on shaping faculty attitude are also addressed. A questionnaire was administered to all faculty members at CBA-KU resulting in a final response of 43 observations. While the one-sample t-test and Pearson correlation were used to investigate faculty attitude and perceived benefits and their level of association, Regression analysis was utilized in testing the effect of perceived benefits on faculty attitudes. Findings revealed a relatively high positive attitude toward AACSB accreditation and a significant above-average level of agreement with all addressed benefit statements. Significant positive correlation between benefits and attitudes and a significant effect of academic benefits on faculty attitude were also confirmed. The study is the first AACSB accreditation survey in Kuwait which enriches the understanding of the value of earning the accreditation and highlights some factors that enhance faculty positive attitude toward AACSB accrediting.